CORRUPTION IS A MAJOR PROBLEM OF COMMUNITY DEVELOPMENT - Bahodirov Avazbek Bahodirovich (Scholar Express Journals, 2022)
In this article we will talk about the main problem of corruption Community Development. The author relied on legal data and written sources, introduced clarifications to the problem on the basis of existing scientific literature, and studied the existing peculiarities of corruption on the main problem of the development of society.
Keywords: corruption; Society; Development; state